Aggregation tailored emission of a benzothiazole based derivative: photostable turn on bioimaging. Issue 68 (4th December 2019) - Kaur, Ishpreet; Sharma, Vinay; Mobin, Shaikh M.; Khajuria, Anjali; Ohri, Puja; Kaur, Paramjit; Singh, Kamaljit
Abstract : A molecular probe is reported that aggregates in a solvent mixture which exhibits emission and has excellent potential for cell and plant tissue imaging. Abstract : Herein, we report a benzothiazole based probe which exhibits aggregation induced emission in mixed solvents, v/v THF : water system. The blue emission observed in the solution is ascribed to the enolic emission of the excited state intramolecular proton transfer (ESIPT) prone benzothiazole chromophore, as the aggregation induced by the protic solvent, water, is expected to restrict the phototautomerization of the probe to the keto form which generally emits in the red region. However, the green emission observed in the solid aggregated state is ascribed to its keto emission, as in the solid state the ESIPT process is activated owing to stable intramolecular hydrogen bonding, giving a keto-aggregation induced emission (AIE) coupled emission. The aggregation process is evident from the particle size and the change in morphology predicted by dynamic light scattering (DLS) and scanning electron microscopy (SEM) respectively, in the aggregated state. Interestingly, the emission in the solution, as well as the solid state, is convincingly mimicked in the fluorescence imaging of various live cancer cells and plant roots.